Pembangunan Model Restaurant Management System - Fredy Jingga; Natalia Limantara (ComTech: Computer, Mathematics and Engineering Applications, 2014)
Model design for Restaurant Management System aims to help in restaurant business process, where Restaurant Management System (RMS) help the waitress and chef could interact each other without paper limitation.  This Restaurant Management System Model develop using Agile Methodology and developed based on PHP Programming Langguage. The database management system is using MySQL. This web-based application model will enable the waitress and the chef to interact in realtime, from the time they accept the customer order until the chef could know what to cook and checklist for the waitress wheter the order is fullfill or not, until the cahsier that will calculate the bill and the payment that they accep from the customer.